Which households matter most? Capturing equity considerations in tax reform via generalised social marginal welfare weights - David Madden; Michael Savage (University College Dublin, UCD School of Economics, 2015)
Social marginal welfare weights play an important role in areas of applied public policy analysis such as tax reform. These weights reflect the values of the social planner, or equivalently the underlying social welfare function. A number of recent papers have questioned the "default" Utilitarian-based approach used to derive these weights, and have suggested potential alternatives. However, there are few examples applying these alternative weighting schemes to traditional, nationally representative, datasets, and in particular, few comparisons of how these alternative weighting schemes would affect the distribution of the welfare effects of a specific tax reform in comparison to the Utilitarian-based approach. This paper aims to fill that gap. Using the nationally representative 2009/10 Irish Household Budget Survey, we apply a range of alternatives to Utilitarianism in determining the distribution of social marginal welfare weights, and compare these distributions to that arising from the traditional Utilitarian approach. The alternative weighting schemes we analyse are based upon: the principles of Equal Sacrifice, poverty alleviation, government self-interest and the redistribution of "luck" income. The distribution of welfare weights arising from these approaches are found to differ appreciably from the distribution based upon Utilitarian weights. A simple indirect tax reform model is estimated and applied to the different distributions of welfare weights to investigate the sensitivity of tax reform recommendations to these distributions. Given the importance of social marginal welfare weights in areas of public policy analysis such as optimal labour and commodity tax design, and tax reform evaluation, we believe this detailed examination of the alternatives to Utilitarianism, and their application to a household budget survey dataset, is an important addition to the literature.
Keywords: D31; D6; D71; H21; H23; 330